Interconnective Approach in Building Harmonious Religious and State Relationships in A Pluralistic Society - Maulana, M Hasan; Baihaqi, M Ahnaf; Abdilla, M Risqi; Septiawan, M Rifky; Bilbina, Alya Putri; Kamaludin, Afif; Adzim, Abdul (International Tatho Academics, 2025)
The purpose of this study is to explore Amin Abdullah's interconnective approach and its contribution to the understanding and practice of inclusive, and contextual religious life in a pluralistic society. This research uses a qualitative approach in the form of a literature study, analyzing Abdullah's works and thoughts theoretically and conceptually. The results of the study show that Amin Abdullah rejects the dichotomy between religion and the state and encourages religion to be present as a constructive social force in the public sphere through an interdisciplinary and connected epistemology. In practice, this approach encourages religious and educational institutions to expand their social roles and interfaith dialogue. This research contributes to the importance of an integrative and contextual approach in building a civilization of religious and state